Synergistic effect of phytochemicals on cholesterol metabolism and lipid accumulation in HepG2 cells - Ennian Leng; Yuan Xiao; Zhentao Mo; Yiqi Li; Yueyue Zhang; Xiaosi Deng; Min Zhou; Chaochao Zhou; Zengxuan He; Jingyi He; Lu Xiao; Junming Li; et al. (BMC, 2018)
Abstract Background Crocin (CRO), chlorogenic acid (CGA), geniposide (GEN), and quercetin (QUE) are all natural compounds with anti-obesity properties, in particular, hypolipidemic effects, which have been widely used for the treatment of obesity-related metabolic diseases. However, it is not yet known whether these compounds interact synergistically. Here, we investigated the effects and molecular mechanisms of CRO, CGA, GEN, QUE, and a combination of all four compounds (CCGQ), on lipid accumulation in human hepatoma (HepG2 cells). Methods The optimal concentration of CRO, CGA, GEN, QUE to stimulate HepG2 cells proliferation was determined using MTT assay. HepG2 cells were pretreated with 10 μmol/L simvastatin, 1 μmol/L CRO, 30 μmol/L CGA, 10 μmol/L GEN, 10 μmol/L QUE, and CCGQ (a combination of 1 μmol/L CRO, 30 μmol/L CGA, 10 μmol/L GEN, and 10 μmol/L QUE) for 24 or 48 h. Oil red O staining and extracellular TC and TG levels were detected. The RT-PCR was used to observe on cholesterol metabolism-related gene expression. Immunocytochemistry and western-blot assayed the 3-hydroxy-3-methylglutaryl-coenzyme (HMGCR) protein expression in HepG2 cells. Results Compared to those of control, we demonstrated that treating HepG2 cells for 48 h with CCGQ resulted in a strong synergistic effect, causing a marked decrease in lipid deposition in comparison to individual treatments, in both triglyceride and total cholesterol (CRO, 5.74- and 1.49-folds; CGA, 3.38- and 1.12-folds; GEN, 4.04- and 1.44-folds; QUE, 3.36- and 1.24-folds; simvastatin, 5.49- and 1.83-folds; and CCGQ, 7.75- and 2.20-folds), and Oil red O staining assays. In addition, CCGQ treatment increased ATP-binding cassette transporter (ABCA1), cholesterol 7α-hydroxylase (CYP7A1), and AMP-activated protein kinase 2α (AMPKα2) mRNA expression, while decreasing sterol regulatory element binding protein 2 (SREBP2), and liver X receptor alpha (LXRα) mRNA expression. Notably, CCGQ was more effective in decreasing HMGCR expression than the individual treatments. Conclusion The CCGQ combination has potential, both as a complementary therapy for hyperlipemia, and in preventing further obesity-related complications.